Shaping Student Character Through Daily Life Activities: Study of Female Students at Wisma Alamanda - Zainul Arifin; Riska Lestari; Lisani Husna; Rustiya Rustiya (International Journal of Multidisciplinary Research of Higher Education, 2020)
The activities of students who live in a wisma are certainly different from students who live in houses, boarding houses, or dormitories. This is of course very influential on the character possessed by students. The aim of this study is to find out how the efforts made in building the character of students living in Wisma. This research uses the method qualitative approach with a case study. The research data was taken from three informants who are students who live in Wisma through in-depth interviews. To strengthen the data, the authors also made direct observations of students living in Wisma. Research result shows that there are seven important themes in the effort to build student character at Wisma. The seven themes are implemented through: i) wisma rules (discipline, responsibility, independence), ii) social activities (tolerance, social care), iii) spiritual activities (religious, curious), iv) joint activities (honest, creative, democratic, appreciate achievement, friendly, loves peace, cares for the environment), v) daily worship practices (religious, hard work), vi) national day commemoration (national spirit, love of country), vii) Channeling interest in reading (likes to read). The results of this study can be used as information for students to be able to build character in everyday life.